Cushions of Thylacospermum caespitosum (Caryophyllaceae) do not facilitate other plants under extreme altitude and dry conditions in the north-west Himalayas - de Bello, Francesco (Oxford University Press, 2011)
BACKGROUND: Cushion plants are commonly considered as keystone nurse species that ameliorate the harsh conditions they inhabit in alpine ecosystems, thus facilitating other species and increasing alpine plant biodiversity. A literature search resulted in 25 key studies showing overwhelming facilitative effects of different cushion plants and hypothesizing greater facilitation with increased environmental severity (i.e. higher altitude and/or lower rainfall). At the same time, emerging ecological theory alongside the cushion-specific literature suggests that facilitation might not always occur under extreme environmental conditions, and especially under high altitude and dryness. METHODS: To assess these hypotheses, possible nursing effects of Thylacospermum caespitosum (Caryophyllaceae) were examined at extremely high altitude (5900 m a.s.l.) and in dry conditions (precipitation <100 mm year(−1)) in Eastern Ladakh, Trans-Himalaya. This is, by far, the highest site, and the second driest, at which the effects of cushions have been studied so far. KEY RESULTS: In accordance with the theoretical predictions, no nursing effects of T. caespitosum on other alpine plants were detected. The number and abundance of species were greater outside cushions than within and on the edge of cushions. None of the 13 species detected was positively associated with cushions, while nine of them were negatively associated. Plant diversity increased with the size of the area sampled outside cushions, but no species–area relationship was found within cushions. CONCLUSIONS: The results support the emerging theoretical prediction of restricted facilitative effects under extreme combinations of cold and dryness, integrating these ideas in the context of the ecology of cushion plants. This evidence suggests that cases of missing strong facilitation are likely to be found in other extreme alpine conditions.